1993
DOI: 10.1007/bf01954097
|View full text |Cite
|
Sign up to set email alerts
|

Discrete membranous subaortic stenosis in siblings

Abstract: References E1 Habbal MH (1991) Discrete subaortic stenosis in a newborn. PediatrCardiol 12 : 243-244 2. Gale AW, Cartmill TB, Bernstein L (1974) Familial subaortic membranous stenosis. Aust NZ J Med 4:576-581 3. Gewillig M, Daenen W, Dumoulin M, Van der Hauwaert L (1992) Sir: Discrete membranous subaortic stenosis (DMSS) is an uncommon cardiac defect occurring mostly as an isolated lesion of obscure aetiology [3]. We investigated two sisters affected by DMSS whose parents were unaffected, but were second cousi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Previously published studies have demonstrated that the mode of inheritance for SAS in dogs is complex and variable [ 5 , 6 ]. This is similar to humans, in which an autosomal recessive as well as an autosomal dominant mode of inheritance was reported previously [ 18 20 ]. In dogs, pedigree evaluation was also completed for other dog breeds, with a high prevalence for this disease [ 33 ].…”
Section: Introductionsupporting
confidence: 91%
“…Previously published studies have demonstrated that the mode of inheritance for SAS in dogs is complex and variable [ 5 , 6 ]. This is similar to humans, in which an autosomal recessive as well as an autosomal dominant mode of inheritance was reported previously [ 18 20 ]. In dogs, pedigree evaluation was also completed for other dog breeds, with a high prevalence for this disease [ 33 ].…”
Section: Introductionsupporting
confidence: 91%
“…30,65,66,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] Other supportive findings include the fact that some cases, admittedly uncommonly, are diagnosed in the neonatal period, [86][87][88][89] there is well-recognised recurrence in siblings, 84 and the fact that some patients with fixed subaortic stenosis have been born to nonaffected but consanguineous parents. On the basis of these observations, it has been suggested that fixed subaortic stenosis could be the result of an autosomal recessive mutation 90,91 (Table 2). From the stance of the dog, Patterson, his colleagues, and others, have discussed extensively the epidemiologic and genetic aspects of cardiovascular development, [4][5][6][7]10,94,95 while Mulvihill and Priester 97 have reiterated the similarities between canine and human congenital cardiac disease.…”
Section: Fixed Subaortic Stenosis: Congenital or Acquired?mentioning
confidence: 99%
“…12 The ever increasing number nowadays of patients with severe defects surviving surgical intervention have also shown that the incidence of cardiac malformations in the offspring of affected parents is higher than had been previously expected, supporting a proposed monogenic inheritance for many cardiac defects. 13 A mendelian transmission has been identified for some specific isolated cardiac malformations, including hypertrophic cardiomyopathy, 14 supravalvar aortic stenosis, 15 "conotruncal" defects, 16 ' 17 atrioventricular canal defects, 18 -19 discrete subaortic stenosis, 20 and patency of the arterial duct. 21 It has now become possible to delineate the genetic defect of such familial cardiac malformations through linkage analysis and positional cloning.…”
mentioning
confidence: 99%